DETERMINAN GANGGUAN KEPEKAAN KULIT PADA PETANI BAWANG MERAH DESA WANASARI KECAMATAN WANASARI KABUPATEN BREBES - Naftani Chandra Dini; Nurjazuli Nurjazuli; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The whole of onion farmers in Wanasari Village are using pesticide in minimum third times in one week through two months on onion planting dates. In long term exposure, the chemical ingredients in pesticide can affect chronical effect, such as loss of skin sensitivity that will led into the beginning of more serious disease. In primary research, it showed that there were 2 of 5 farmers have had skin sensitivity disorder. The aim of this research was to determine factors that affect skin sensitivity disorder among onion farmers in Wanasari Village. This research was conduct observational with cross sectional design. The population in this research was the whole of farmers in Wanasari Village onion farmland’s with 40 samples which derived by propotional cluster random sampling method. The data analysis was using chi square test. According to skin sensitivity disorder test, it showed that 25 of 45 respondents have had skin sensitivity disorder. The result of bivariate analysis showed that variable which has relationship with skin sensitivity disorder among onion farmers were PPE using, the duration of work, and personal hygiene. This research showed that 55,6% respondents have hadskin sensitivity disorder and there were relationship between PPE using (p-value 0,015; POR 2,429; CI = 1,121-5,260), duration of work (p-value 0,032; POR 2,111; CI = 1,051-4,241), and personal hygiene (p-value 0,0001; POR 3,958; CI = 1,956-8,009) with skin sensitivity disorder among onion farmers in Wanasari Village. Researcher recommends to respondents to pay attention in hygiene and health during working with using PPE and conduct working time limitation in onion farmland.